Tradiciones electivas: cambio, continuidad y ruptura en historia intelectual (Almanack, 2022)
This essay begins by questioning certain common places regarding suchdichotomies as modernity vs. tradition, rupture vs. continuity, stereotypesstill circulating among those historians who present a direct oppositionbetween both poles, as if they were radically incompatible factors,mutually exclusive vectors. To this end, it emphasizes the dynamic natureand the productive dimension of tradition, understood to be a fundamentalingredient and irreplaceable mechanism in processes of change andintellectual innovation. The article underlines the fact that modern times –and their revolutions – are a prolific laboratory of what the author calls“elective traditions”. By means of these, diverse collective actors in themaking – political parties and ideological movements, nations, classes,etcetera – build themselves, adopting different ad hoc pasts: from thevariegated store of the past, their leaders and ideologists select certaincharacters, events and canonical texts with which they shape narrativeidentities, long-term historical currents and ongoing trajectories in whichthese actors identify themselves and to which they subscribe with a view to legitimizing their future projects. In this way, the moderns choose theirpurported predecessors, presenting themselves as their heirs. The focus of“elective traditions”, this article suggests, might shed light upon certainaspects of the history of ideologies and of political and social movementsin recent centuries.